2023
DOI: 10.52711/2231-5675.2023.00008
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Gas Chromatography

Abstract: Gas Chromatography (GC In gas chromatography, the components of a sample are dissolved in a solvent and vaporized in order to separate the analytes by distributing the sample between two phases: a stationary phase and a mobile phase) is a normally utilized analytic technique as a part of numerous research and industrial research facilities for quality control and in addition identification and quantitation of components in a mixture Mass spectroscopy is an advanced and powerful technique for qualitative and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the present study, we observed the amelioration of various oxidative stress biomarkers in multiple organs after COE co-treatment with doxorubicin. Moreover, our previous studies also support the efficacy of COE in ameliorating oxidative stress and cancer progression (Patil et al, 2022b;2022a). Emmanuel et al reported that cocoa leaf polyphenolic-rich extract inhibited xanthine oxidase due to the flavonoids and phenolic acids present in the extract (Irondi et al, 2017).…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we observed the amelioration of various oxidative stress biomarkers in multiple organs after COE co-treatment with doxorubicin. Moreover, our previous studies also support the efficacy of COE in ameliorating oxidative stress and cancer progression (Patil et al, 2022b;2022a). Emmanuel et al reported that cocoa leaf polyphenolic-rich extract inhibited xanthine oxidase due to the flavonoids and phenolic acids present in the extract (Irondi et al, 2017).…”
Section: Discussionsupporting
confidence: 69%
“…This method boasts high efficiency, providing elevated resolution by detecting in parts per million (ppm) and parts per billion (ppb), and typically requires small sample volumes, usually measured in microliters (μL) (McNair et al, 2019). However, a notable limitation of GC lies in its ability to analyze only volatile samples, and proper handling is imperative for sample injection (Patil et al, 2023).…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…The PGP traits of inorganic phosphate solubilization, organic phosphate solubilization, potassium release, siderophore production and nitrogen fixation were determined on Pikovskaya's agar medium (Pikovskaya, 1948), Mongina organophosphorus culture medium (Hu et al, 2009), potassium bacteria agar medium (Yaghoubi et al, 2021), chrome azurol S (CAS) agar medium (Balasjin et al, 2022) and nitrogen-free Ashby's medium (Patil et al, 2010), respectively. The presence of a transparent zone around the bacterial colony was considered an indicator of a positive reaction for phosphate solubilization or potassium release.…”
Section: Isolation and Characterization Of Endophytic Bacteria With P...mentioning
confidence: 99%